Validation of a Comorbidity Index for Use in Obstetric Patients: A Nationwide Cohort Study. Issue 1 (24th March 2021) - Bliddal, M.; Möller, S.; Vinter, C.A.; Rubin, K.H.; Gagne, J.J.; Pottegård, A.
Abstract : ( Acta Obstet Gynecol Scand . 2020;99:399–405) Severe maternal morbidity associated with childbirth has increased in the last 30 years in the United States. A score to predict risk for maternal morbidity would be useful to help place high-risk women at better-equipped facilities and also address some confounding factors in research. The Obstetric Comorbidity Index (OCI) was developed by Bateman and Gangne to accomplish these goals, but has only been validated in very specific populations. This study used the Danish health registers, which contain complete data on all obstetric patients, to examine the ability of the OCI to predict morbidity and discriminate between low-risk and high-risk obstetric patients for maternal end-organ injury and death.